COMMUNICATION STYLE OF THE 2024 PRESIDENTIAL CANDIDATES - Riswandi, Riswandi; Aunul, Sofia; Putri, Ratu Laura Mulia Baskara (Jurnal Visi Komunikasi, 2025)
Communication style is sometimes more important than the content of the communication. In the context of a country, a president needs to develop a communication style that suits his personality character in order to contribute to the effectiveness of his government. This study aims to describe the communication styles of three presidential candidates—Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto, and to relate them to the tendencies of each individual's personality type. The method used is analyzing documents of news (from Detik.com, Kompas.com and Republika.go.id) with news samples in December 2023-January 2024 highlighting news items that contain the meaning of communication style. The results show that Anies Baswedan's communication style tends to be Argumentative and Precise, Ganjar Pranowo tends to be Open and Impression leaving, while Prabowo Subianto's communication style tends to be Dominant. Based on the tendency of this communication style, Anies Baswedan's personality tends to reflect the Sanguine type, Ganjar Pranowo tends to be Phlegmatic, while Prabowo Subianto tends to be the Choleric type.